THE INFLUENCE OF TEACHER PERCEPTIONS OF ACADEMIC SUPERVISION BY SCHOOL PRINCIPALS AT PUBLIC ELEMENTARY SCHOOLS IN KEI KECIL-SOUTHEAST MALUKU - Meci, Lodovika; Novianto, Victor; Warwefubun, Mufala; Rekol, Mahila (Program Magister Pendidikan IPS UPY, 2025)
research aims to determine the influence of teacher perceptions on academic supervision by school principals at Inpres State Elementary Schools in Kei Kecil District, Southeast Maluku Regency. The research approach uses a quantitative type of research. The population in this study were all teachers at SD Negeri Inpres Ohoijang and SD Negeri Inpres Vatwahan with a total of 46 people. Based on the research results, it shows that the teacher perception variable at Inpres State Elementary Schools in Kei Kecil sub-district, Southeast Maluku district has a sig value < ????, namely 0.001 < 0.05. Then the coefficient of determination value is known to have an R square value of 0.691, namely the influence of teachers' perceptions of academic supervision by school principals at Inpres State Elementary Schools in Kei Kecil sub-district, Southeast Maluku Regency is 69.1%. This means that the influence of teacher perceptions on academic supervision by principals of SD Negeri Inpres in Kei Kecil sub-district, Southeast Maluku district is in the high category out of a total of 100%. This is shown by indicators of teacher perception in terms of knowledge, trust and confidence, as well as having a good attitude. The implementation of academic supervision by school principals is carried out through planning, implementation and follow-up indicators, while the remaining 30.1% is influenced by other factors not included in this research. The implication of this research is that academic supervision by the principal is achieved through teacher perceptions, although there is a strong influence, but it still needs to be improved optimally. Other researchers are advised to add learning innovation variables as the key to educational success in the future. Keywords: teacher perceptions, observations in academic supervision, school principal.